القضية الفلسطينية في فكر الشيخ محمد البشير الابراهيمي - عطالله, عواطف; خلايفة, فتيحة; طاغية, محبوبة; خلايفة, هاجره (جامعة الوادي university of eloued, 2019)
الملخص ان الحديث عن اعظم قضية من قضايا الامة الإسلامية لا يزال الأهم في وجدان الشعوب العربية والإسلامية، فبالرغم من تصاعد المشكلات العربية وازديادها فقد بقيت ام القضايا العربية والجرح الذي ينزف حتى الان، وقد اخذت حيزا كبيرا في مواقف الشيخ الابراهيمي وبياناته وفي كتاباته بجريدة البصائر، وبعض ماعبر عليه في أوراقه الشخصية جمعت في اثاره حيث تناولها من مختلف جوانبها . Summary The talk of the greatest issue of the Muslim Ummah is still the most important in the minds of the Arab and Islamic peoples. Despite the escalation of Arab problems and their increase، the Arab issues have remained، and the wound that is bleeding so far، has taken a great place in the positions of Sheikh Ibrahimi and his statements in his writings in Al-Busayir newspaper، Passing it in his personal papers collected in its effects، where it addressed from various aspects.
دعوة